2002
DOI: 10.1088/0954-3899/28/2/306
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous time structure of extensive air shower particle flows in the knee region of primary cosmic ray spectrum

Abstract: We observe the new phenomenon of anomalous prolonged time distributions of neutron intensity using the 18NM64-type neutron monitor operating together with the shower installation of the Tian-Shan mountain cosmic ray station. We observe anomalous events in the core region of extensive air showers (EAS) with the size Ne > 106. The threshold of their generation coincides with the ‘knee’ in the energy spectrum of primary cosmic rays (about 3 × 1015 eV). The prolonged neutron events are accompanied by the flows of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 8 publications
(16 reference statements)
3
53
0
1
Order By: Relevance
“…However, the discovery of neutrons delayed by hundreds microseconds in the shower core made by Chubenko A.P. and his group with the Tien-Shan neutron monitor [38,39,40,41,42] seemed to be unexpected and attracted an attention [43,44,45,46,47].…”
Section: Interactions Of Eas With Detectors and An Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the discovery of neutrons delayed by hundreds microseconds in the shower core made by Chubenko A.P. and his group with the Tien-Shan neutron monitor [38,39,40,41,42] seemed to be unexpected and attracted an attention [43,44,45,46,47].…”
Section: Interactions Of Eas With Detectors and An Environmentmentioning
confidence: 99%
“…However, the experimental study of the neutron 'thunder' revealed that delayed neutrons are accompanied by gamma-quanta and electrons [41], which in principle could give a signal in water tanks.…”
Section: Interactions Of Eas With Detectors and An Environmentmentioning
confidence: 99%
“…The distributions presented in [8] indicate that their distortions have most likely a methodical explanation connected with the 'saturation' of neutron counting rate at the high neutron intensities. The arguments for that conclusion are the following: (i) the maximum 'saturation' counting rate of the standard neutron monitor unit with 6 counters of SNM15 type ( the dead time τ ≈ 2µs ) is expected as 6/τ ≈ 3µs −1 ; (ii) this saturation is expected to start close to the observed neutron multiplicity…”
Section: The Change Of the Temporal Distributionmentioning
confidence: 90%
“…In the detailed study [8] of the effect it has been claimed that the process has a threshold and the delayed neutrons appear at PeV primary energies, i.e. in the region of the 'knee' observed in the primary cosmic-ray ( CR ) energy spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Typically for these events is the instantaneous generation of an extremely large number (up to some thousands) of evaporation neutrons as an interaction result of energetic EAS core hadrons with monitor substances; later on, these neutrons are quickly thermalized and diffuse in the monitor during some milliseconds [5]. The MCU acquisition program permits to trace the events of such a type in the current signal flow, and to precisely register the time behavior of neutron intensity with 10-30 µs resolution over the time of some milliseconds uninterruptedly, which functionality, again, goes on in parallel and independently on the basic counting rate measurements.…”
Section: Isvhecri 2016mentioning
confidence: 99%